The Role of Digital Technologies on Women’s Empowerment and Economic Inclusion in Turkey - Tan, Basak Ucanok (IGI Global, 2025)
This chapter explores the role of digital technologies in women’s empowerment and economic development in Turkey. Digitalization, the availability of social technology platforms, and knowledge regarding the benefits of these platforms open doors to employment and economic growth for women. Digitalization cannot guarantee women’s empowerment and eradicate gender inequalities if not policies for reducing the gender digital divide are not prioritized. Thus, the chapter highlights the potential of digital technologies in combatting the gender gap and enhancing women’s empowerment. © 2025 by IGI Global Scientific Publishing.
Keywords: Digital Divide; Digital Technologies; Economic Development; Economic Growths; Employment Growth; Open Doors; Social Technologies; Technology Platforms